Powerphys - Allen, Connie; Harper, Valerie ([s.l] : John Wiley & Sons, 2007)
PowerPhy is a program of activities developed to simulate laboratory experiences that illuminate important physiological processes and their implications for maintaining homeostasis
System requirements for Mac Os X: G4 PowerPc, 256 MB RAM, 2x speed CD-ROM drive, 1024 x 768 resolution, hi-color mode, MacOS X versions 10.2.8 and above, Safari 1.0 and above, Firefox 1.0 and above
System requirements for PC: Pentium III or higher, 256 MB RAM, 4x speed CD-ROM drive, 1024 x 768 screen resolution, hi-color mode, Windows ME, Windows 2000, Windows NT4 (SP), Windows XP, Windows compatible sound card, Internet Explorer 5.5 and above or Firefox 1.0 and above
Keywords: Anatomy -- Laboratory manuals; Physiology -- Laboratory manuals